SINERGY OF INTRINSIC ELEMENTS OF THE SHORT STORY MEMAHAT CINTA DI RINJANI - Iwan Sulistiawan (Journal of Innovation Research and Knowledge, 2024)
This research aims to see the intrinsic elements of the short story, Memahat Cinta di Rinjani by Lina W. Sasmita. By focusing on studying four intrinsic elements; plot, characterization, setting and theme, as well as other supporting elements, utilizing qualitative descriptive research methods and point of view from theories regarding the analysis of intrinsic elements of literary works, this research seeks to answer two research questions, namely whether there are the accuracy of the arrangement of the four intrinsic elements and the synergy between the three elements to support the entire story. The findings of the reserch show that the four elements are arranged correctly and the synergy between the four elements is mutually attached and it supports the aesthetics of the stories